Digitalization Potential in Production Sphere - S. B. Baurina (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
Global virtualization of production, new challenges and goals of society informatization made today’s production companies change their own production processes in order to retain competitiveness on market. Standard approaches to production management now cannot guarantee stable profitability of business. The concept of smartproduction and wise factories targets at integration of people, information and value chains in one network. It can provide a new impulse to labour productivity, predetermine new opportunities for improving the work efficiency. Today’s foreign and home literature shows academic interest in new production technologies. In spite of various trends and approaches to the subject, principle priorities of advanced smart production processes have not been revealed adequately, which proves the necessity to continue research in this field. The article substantiates the demand for production process digitalization at Russian enterprises. Possibilities of using artificial intellect and introducing smart-production in industry are studied. Priorities of the advanced Russian production companies in the field of digitalization were highlighted: wider use of cloud technologies; predictive analysis; IaaS-services, i. e. virtual centers of data processing and systems of data storage; centralized dispatcher control and data collection (SCADA) and others. The author characterizes parameters of monitoring development of smart production systems on the territory of the Russian Federation, which has been carried out by Rosstat since 2020. The forecast data on assessing the required resources in respect to support tools on behalf of state were shown, aimed at developing technologies of smart production. Target indicators of developing smart technologies were identified within the frames of the federal project ‘Digital Technologies’. The author systematized science-intensive technological innovations, non-standard solutions and advanced tools of managing production systems, specified target indicators of principle technological trends in smart-production development and substantiated lines in the development of smart-potential of Russian industry.